Der Islam als akademische Praxis Von der biographischen Islamizität zum pluralen Islam - Dreier, Lena (Religion in der Gesellschaft, 2023)
The subject Islamic theology, which was founded eleven years ago, was politically expected to train imams who promote integration. The author empirically investigates how students of Islamic theology deal with these expectations. The book shows that the actors' attributions of meaning is interwoven with the state's approach to religion and the academic discipline's approach to Islam. The result is the concept of biographical Islamicity, i.e. a central mode of experience of Muslims in minority contexts. The actors institutionalise the image of a plural Islam. The book provides a sociological contribution to the discussions about religious-secular constellations in the society.